The Effectiveness of Basic Physics Experiment Module Based on Guided Inquiry Model in Improving Hard Skills and Soft Skills of Prospective Physics Teachers - Suprianto, S.; Kholida, S. I.; Andi, H. J.; Mahardika, I. K. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
The purpose of this research is to identify the effectiveness of the first basic physics practice module based on guided inquiry on improving students’ hard skills and soft skills. The experimental design is